THE INDONESIAN BANKING INDUSTRY COMPETITION: FINANCIAL CONGLOMERATION APPROACH - Dyah Nirmalawati Taurusianingsih (MIX: JURNAL ILMIAH MANAJEMEN, 2016)
Abstract. This study was conducted to analyze the existence of economies ofscope and competition in the Indonesian banking industry based on thephenomenon of financial conglomerates. By using the New Empirical IndustrialOrganization method, this study contributed to enrich the literature of bankingindustry competition in Indonesia. The results of the study showed thatconglomeration increased market power and decreased market level competition.